Thing explainer : complicated stuff in simple words - Munroe, Randall (Houghton Mifflin Harcourt, 2015)
The creator of the popular webcomic "xkcd" uses line drawings and just ten hundred common words to provide simple explanations for how things work, including microwaves, bridges, tectonic plates, the solar system, the periodic table, helicopters, and other essential concepts.